2017
DOI: 10.1371/journal.pntd.0005675
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-4 receptor alpha is still required after Th2 polarization for the maintenance and the recall of protective immunity to Nematode infection

Abstract: There is currently no vaccine against parasitic nematodes and the knowledge on the mechanisms by which protective immunity against this class of parasites is achieved is continuously expanding. Nematode parasites trigger a host protective type 2 immune response via interleukin-4 receptor alpha (IL-4Rα). Despite this central role, it is not known whether IL-4Rα has a role in maintaining host type 2 immune responses following polarization. To determine the role of IL-4Rα after polarization, we used a recently es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
(61 reference statements)
0
13
0
Order By: Relevance
“…Infections with parasitic worms induce a T helper type 2 (Th2) immune response that is important for controlling parasite burdens during primary infection and for immunity to subsequent secondary infections [14]. Additionally, Th2 immune responses have evolved to rapidly repair tissue damage caused by parasitic worms, and to restore tissue integrity and homeostasis following parasite killing [57].…”
Section: Introductionmentioning
confidence: 99%
“…Infections with parasitic worms induce a T helper type 2 (Th2) immune response that is important for controlling parasite burdens during primary infection and for immunity to subsequent secondary infections [14]. Additionally, Th2 immune responses have evolved to rapidly repair tissue damage caused by parasitic worms, and to restore tissue integrity and homeostasis following parasite killing [57].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies aimed at elucidating the immunological factors driving host protective immunity to schistosomiasis took advantage of constitutive gene-deficient mouse models. These studies demonstrated that T and B cells (17–21) and Th2 effector molecules (IL-4, IL-13, IL-10, IL-4Rα, STAT-6) are crucial for conferring host protective immunity to infection (22–31). In our laboratory, we have looked in more detail at the cell-specific requirements of IL-4Rα in driving host survival during S. mansoni infection.…”
Section: Introductionmentioning
confidence: 99%
“…The immune response to schistosomiasis, similarly to that against other tissue-dwelling helminth infections [ 4 6 ], is highly polarized as it progresses, going from i) an early Th1 response to ii) a powerful Th2 response that culminates as the adult parasite-released eggs are trapped in the host tissues [ 2 , 3 ] and finally iii) a chronic regulatory phase with a minimized but still dominant Th2 response [ 3 , 7 , 8 ] with a more clinically relevant tissue fibroproliferative pathology. Our current understanding of schistosomiasis pathology heavily relies on the use of experimental murine models [ 2 ].…”
Section: Introductionmentioning
confidence: 99%